The Effect of Work Experience, Performance Management for Knowledge-Skill-Attitude and Positive Vibes on the Leadership Model - Monica Dyah Untari; Muhammad Sholahuddin (Yayasan Riset dan Pengembangan Intelektual, 2023)
In an organization, teamwork plays a critical role. Experience, management knowledge, and a positive work environment can aid companies in developing leadership models as they are integral components of Human Resource Management. Experience, Knowledge Management and Positive Vibes will be aspects that affect employee performance. This research aims to develop existing leadership models among employees. It falls under qualitative research focusing on gaining an in-depth understanding of aspects of business operations related to employee performance. The population studied were employees within a company with 37 samples taken for analysis purposes.The analytical method employed is multiple linear regression with the help of SPSS software. The results indicate that both Experience and Performance Management for Knowledge Skill Attitude influence leadership models which underscores the importance of these factors in shaping effective leadership.